Evaluation of lipoprotein(a) — a novel cardiovascular risk factor in patients with atherosclerotic cardiovascular diseases receiving PCSK9-targeted therapy in Russian real-world practice - A. I. Sapina; Yu. Yu. Varlamova; M. G. Papyrina; A. S. Bezymyannyy; E. L. Kordzaya; E. Yu. Vasilyeva (Российский кардиологический журнал, 2025)
Aim. To evaluate the effect of PCSK9-targeted therapy on lipoprotein(a) (Lp(a)) levels in patients with atherosclerotic cardiovascular diseases who have not achieved the target low-density lipoprotein cholesterol (LDL-C) level (statins at maximum tolerated doses and/or ezetimibe).Material and methods. The study involved 3 Moscow medical facilities of the state healthcare system. The study included 50 people who received inclisiran therapy, 30 people — PCSK9 inhibitors (alirocumab, n=1; evolocumab, n=29). This analysis presents the results of Lp(a) level changes over 12-month inclisiran therapy. Lp(a) was determined by turbidimetry. Elevated Lp(a) level was defined as ≥50 mg/dL (125 nmol/L).Results. Normal Lp(a) levels were determined in 16 subjects (34,8%), moderate — in 9 subjects (19,6%), high — in 21 subjects (45,7%), and extremely high (>180 mg/dL) — in 8 subjects (17,4%). Inclisiran therapy was associated with a significant (p<0,001) decrease in both LDL-C and Lp(a) levels by 52% and 54,7%, respectively. During therapy, normal Lp(a) levels remained within baseline values. In almost half of the cases with moderate Lp(a) values, its concentration decreased to normal values, and in cases with elevated Lp(a), its level decreased in 9 out of 10 patients. The proportion of patients in the group with Lp(a) levels <30 mg/dl increased from 35% to 41%. No patient had extreme values by the end of the study.Conclusion. Lp(a) assessment may be appropriate with ongoing PSCK9-targeted therapy. Diagnosis of hyper-Lp(a) is important for early intensive combination lipid-lowering therapy and modification of risk factors in order to reduce the risk of cardiovascular diseases.